COMPARING THE EARTHQUAKE EXPOSED AND NON-EXPOSED TURKISH CHILDREN’S POST TRAUMATIC STRESS REACTIONS - Bulut, Sefa (Anales de Psicología / Annals of Psychology, 2006)
Unfortunately, Turkey is stretched out on the earthquake fault line; therefore, Turkish children are at risk of developing posttraumatic stress disorder (PTSD) caused by earthquake exposures and the threats of the anticipated earthquakes as well as aftershocks. This current study aimed at identifying PTSD reactions of disaster exposed and non-exposed Turkish children after the big 1999 Marmara earthquakes in the two cities as Sakarya and Edirne, Turkey. The data for both of the trauma and control groups were collected in May of 2000. OSU-Child PTSD Inventory was used for assessing the PTSD symptoms. The descriptive statistics and independent samples t tests were utilized to compare the exposed and non-exposed groups in terms of frequencies of PTSD diagnosis in mild, moderate, severe and very severe category. The results indicated that the estimated prevalence rates of PTSD reached on a very high proportion of 73% in the earthquake exposed group whereas 9% in the non-exposed-control group. The numbers of children for possible the PTSD diagnose in the exposed-trauma groups were 6 times more than in non-exposed-control group, 144 versus 24, respectively. Psychologists and mental health providers should consider these high severity and prevalence rates of PTSD when developing treatment, intervention and prevention programs for children after natural and technological disasters. Results indicates that early screening for identification of PTSD is very important in predicting the lasting effects of PTSD.